PERSEPSI ORANG TUA TERHADAP SURAT EDARAN KEMENDIKBUD TENTANG BELAJAR DARI RUMAH DIMASA PANDEMIC COVID 19 - Dwi Putri, Weni; Fakhruddin, Fakhruddin; Wanto, Deri (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
This study aimed to depict parents’ perceptions of the Ministry of Education and Culture (MOEC) circular about learning from home during Covid-19 pandemic through a case study in Air Bening Village, Dusun III. This was a field study using a descriptive qualitative approach. The data were collected through interviews, observations and documentation for the sake of garnering the data concerning relevant matters. The results of this study demonstrated that parents' perceptions indicated that MOEC circular about learning at home during the Covid-19 pandemic period was felt to be not running effectively and efficiently. It was because in teaching and learning processes parents turned into a teacher who had to be able to master various learning materials. In the meantime, parents did not understand the materials and contents of their children’s assignments due to their low educational backgrounds. Parents complained about online learning implemented by schools because they lacked the mastery of the facilities available on Android, except only for communicating or accessing photos. Even, some were still unable to use Android properly. In addition, internet networks were inadequate, and students or children played more than learned so that during this pandemic students only learned when they had assignments from the teacher. The rest of their time was not used to rehearse the subject matters.